Comprehensive analysis of fibroblast activation protein expression across 23 tumor indications: insights for biomarker development in cancer immunotherapies - Dziadek, Sebastian; Kraxner, Anton; Cheng, Wei-Yi; Ou Yang, Tai-Hsien; Flores, Mike; Theiss, Noah; Tsao, Tsu-Shuen; Andersson, Emilia; Harring, Suzana Vega; Bröske, Ann-Marie E.; Ceppi, Maurizio; Teichgräber, Volker; et al. (Frontiers in Immunology, 2024)
Fibroblast activation protein (FAP), predominantly upregulated in various tumor microenvironments yet scarcely expressed in normal tissues, was analyzed across 1216 tissue samples covering 23 tumor types and 70 subtypes. Elevated FAP levels were notable in breast, pancreatic, esophageal, and lung cancers. Using immunohistochemistry and RNAseq, a correlation between FAP gene and protein expression was found. Evaluating FAP's clinical significance, we assessed 29 cohorts from 12 clinical trials, including both mono and combination therapies with the PD-L1 inhibitor atezolizumab and chemotherapy. A trend links higher FAP expression to poorer prognosis, particularly in RCC, across both treatment arms. However, four cohorts showed improved survival with high FAP, while in four others, FAP had no apparent survival impact. This emphasizes FAP's multifaceted role in therapy response, suggesting its potential as a cancer immunotherapy biomarker.